Stability parameters during refrigerated storage and changes on the microstructure of orange-carrot blend juice processed by high-power ultrasound - Lepaus, Bárbara Morandi; Santos, Anna Karoline Pereira de Oliveira; Spaviero, Arthur Favoretti; Daud, Polliany Strassmann; de São José, Jackline Freitas Brilhante (Frontiers in Sustainable Food Systems, 2022)
The effect of ultrasound treatments (40 kHz; 40, 50, or 60 °C; 5 or 10 min) and thermal treatment (90 °C; 30 sec) on the stability parameters of orange-carrot juice were evaluated. Microscopic structure, particle size distribution, and turbidity were analysed on the first day. Sedimentation and cloudiness were evaluated over 22 days of storage at 7 and 25°C. Changes in microstructure and disruption of the cell wall were evidenced after treatment at 60 °C/10 min. The particle size distribution was heterogeneous with an increase of small particles after ultrasonication. Ultrasonicated and thermal treated samples did not show any differences in turbidity. Cloudiness increased after sonication and decreased over the storage in all samples. Sedimentation process at 7 °C was homogeneous among samples while it was delayed in samples treated with ultrasounds at 60 °C for 10 min. Ultrasound processing improved the quality of juices and can be proposed as a potential novel processing technique for blended vegetable-fruit juices.